Cerebrovascular mortality: trend and seasonality in Brazilian capitals, 2000-2019 - Luis Sauchay Romero; Ludmilla da Silva Viana Jacobson; Sandra de Souza Hacon (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To evaluate the trend and seasonality of cerebrovascular mortality rates in the adult population of Brazilian capitals from 2000 to 2019. METHODS This is an ecological and descriptive study of a time series of mortality due to cerebrovascular causes in adults (≥ 18 years) living in Brazilian capitals from 2000 to 2019, based on the Brazilian Mortality Information System. Descriptive statistical techniques were applied in the exploratory analysis of data and in the summary of specific, standardized rates and ratios by sociodemographic characteristics. The jointpoint regression model was used to estimate the trend of cerebrovascular mortality rates by gender, age groups, and geographic regions. The seasonal variability of rates by geographic regions was estimated using the generalized additive model by smoothing cubic splines. RESULTS People aged over 60 years comprised 77% of all cerebrovascular deaths. Women (52%), white individuals (47%), single people (59%), and those with low schooling (57%, elementary school) predominated in our sample. Recife (20/1,000 inhab.) and Vitória (16/1,000 inhab.) showed the highest crude mortality rates. Recife (49/10,000 inhab.) and Palmas (47/10,000 inhab.) prevailed after we applied standardized rates. Cerebrovascular mortality rates in Brazil show a favorable declining trend for adults of all genders. Seasonality influenced rate increase from July to August in almost all region capitals, except in the North, which rose in March, April, and May. CONCLUSIONS Deaths due to cerebrovascular causes prevailed in older single adults with low schooling. The trend showed a tendency to decline and winter, the greatest risk. Regional differences can support decision-makers in implementing public policies to reduce cerebrovascular mortality.